Local positioning system analysis of physical demands during official matches in the Spanish futsal league - Serrano, C.; Felipe, J. L.; Garcia-Unanue, J.; Ibañez, E.; Hernando, E.; Gallardo, L.; Sanchez-Sanchez, J. (Sensors, 2020)
The aim of this study was to analyze the influence of the match half and the playing position on physical requirements in the Spanish Professional Futsal League players during official games. The external load from distance, speed, acceleration and deceleration variables were obtained from fourteen elite futsal players during 10 official matches of the 2019-2020 season using a Local Positioning System with ultra-wideband technology installed on the futsal pitch. The results revealed similar results from physical requirements between first and second half (p > 0.05). Wingers demonstrated greater high-speed running distance (+4.04 m·min-1; CI95%: 0.35 to 7.72; ES: 0.87) than pivots (p > 0.05). There were a high number of accelerations (7.42-9.41 n·min-1) and decelerations (7.37-9.12 n·min-1) per minute in all player positions. The principal finding of the current manuscript did not evidence differences in the physical performance of players between the first and second half. The physical requirements varied among pivots and wingers regarding high-intensity actions. These outcomes add new contributions to the understanding of futsal physical demands.